A systematic review of the factors predicting the interest in cosmetic plastic surgery - Panagiotis Milothridis; Leonidas Pavlidis; Anna-Bettina Haidich; Efharis Panagopoulou (Indian Journal of Plastic Surgery)
Background: A systematic review of the literature was performed to clarify the psychosocial characteristics of patients who have an interest in cosmetic plastic surgery. Methods: Medical literature was reviewed by two independent researchers, and a third reviewer evaluated their results. Results: Twelve studies addressing the predictors of interest in cosmetic surgery were finally identified and analysed. Interest in cosmetic surgery was associated with epidemiological factors, their social networks, their psychological characteristics, such as body image, self-esteem and other personality traits and for specific psychopathology and found that these may either positively or negatively predict their motivation to seek and undergo a cosmetic procedure. Conclusions: The review examined the psychosocial characteristics associated with an interest in cosmetic surgery. Understanding cosmetic patients’ characteristics, motivation and expectation for surgery is an important aspect of their clinical care to identify those patients more likely to benefit most from the procedure.